Regular Endurance Exercise Promotes Fission, Mitophagy, and Oxidative Phosphorylation in Human Skeletal Muscle Independently of Age - Balan, Estelle; Schwalm, Céline; Naslain, Damien; Nielens, Henri; Francaux, Marc; Deldicque, Louise (Frontiers in Physiology, 2019)
This study investigated whether regular endurance exercise maintains basal mitophagy and mitochondrial function during aging. Mitochondrial proteins and total mRNA were isolated from vastus lateralis biopsies (n=33) of young sedentary (YS), old sedentary (OS), young active (YA) and old active (OA) men. Markers for mitophagy, fission, fusion, mitogenesis and mitochondrial metabolism were assessed using qRT-PCR, Western blot and immunofluorescence staining. Independently of age, fission protein Fis1 was higher in active vs sedentary subjects (+80%; P<0.05). Mitophagy protein PARKIN was more elevated in OA than in OS (+145%; P=0.0026). mRNA expression of Beclin1 and Gabarap, involved in autophagosomes synthesis, were lower in OS compared to YS and OA (P<0.05). Fusion and oxidative phosphorylation proteins were globally more elevated in the active groups (P<0.05), while COx activity was only higher in OA than in OS (P=0.032). Transcriptional regulation of mitogenesis did not vary with age or exercise. In conclusion, physically active lifestyle seems to participate in the maintenance of lifelong mitochondrial quality control by increasing fission and mitophagy.